KAJIAN KERAGAMAN GENETIK GEN PENYANDI NADH Dehydrogenase Sub-unit 6 (ND6) PADA Tarsius bancanus DAN Tarsius spectrum - , HANUNG PERTIWI, Dr. drh. Rini Widayanti, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tarsius is an endemic primate in Indonesia but is is getting threatened. Insitu and ex-situ conservation of this primate would yield better results when its genetic information and diversity determined. The main objective of this research is to analyze the genetic diversity in Tarsius sp. based on sequences of NADH dehydrogenase sub-unit 6 (ND6) encoding gene.The DNA samples were isolated from muscle of T. bancanus and T. spectrum. Samples then amplificated with Polymerase Chain Reaction (PCR) technique used ND6 Foward and ND6 Reverse primer for T. bancanus samples and ND6 Foward lama and ND6 Reverse primer for T. spectrum samples. The PCR reaction produced 566 base pair (bp) (T. bancanus) and 629 bp (T. spectrum) which than sequenced. Sequencing result then analyzed using MEGA 5.05 version program and compared with some other Tarsius sp. species obtained from Genbank. Result of this research showed there were 118 sites of different nucleotides and 40 different amino acid sites. The average distance of genetic based on nucleotide sequence was 14% and based on amino acid sequence was 15%. Construction of phylogeny tree based on nucleotide and amino acid of ND6 gene with Neighbor-Joining method with bootstrap values 1000 times was able to distinguish between T. bancanus (from Kalimantan) and T. spectrum (from North Sulawesi).